Clinical profile and outcome of poisoning in children admitted to a tertiary referral center in South India - Vasanthan, Mullai; James, Saji; Shuba, S; Abhinayaa, J; Sivaprakasam, Elayaraja (Indian Journal of Child Health, 2015)
Background: Childhood poisoning covers the entire gamut from accidental ingestion in toddlers and preschool children to intentional overdosage in adolescents. The poisons range from fuel to drugs and other chemicals. Objective: To determine the epidemiology, clinical profile, and outcome of children presenting with acute poisoning in a tertiary care center in south India. Materials and Methods: All patients from the age of 1 month to 18 years, admitted during the 1-year study period with a history of poisoning, were included. Animal bites, snake, and scorpion envenomation were excluded. The data were analyzed using SPSS software, version 16. A multivariate analysis was also done and a p<0.05 was considerer significant. Results: There were 75 cases of poisoning out of the total 4074 admissions. Accidental poisoning constituted 73.3% cases and the remaining 26.7% were suicidal. In most of the cases, poisoning was due to fuel (28%) or drugs (21.3%), and kerosene oil was the most common causative substance (28.0%) followed by camphor (14.7%). The higher incidence of poisoning was found in lower middle socio-economic class (56.0%). An analysis of the outcome showed that 92.0% were discharged home, 4.0% with sequelae, and death in 4.0% cases. Conclusion: The highest incidence of poisoning was observed in the lower middle socio-economic group. Most of the poisons were household products, and the most common nature of exposure was accidental. In most of the cases, recovery was complete.